Amino Acid Levelsin the Brain of Rats with Peripheral Nerve Constriction or Section - Mauro Bianchi; Paolo Ferrario; Antonio Clavenna; Gabriele Biella; Maria Luisa Sotgiu (Pain Research and Management)
BACKGROUND: Both excitatory and inhibitory amino acids modulate central neuronal activity following peripheral nerve tissue injury.